E‐CHAIM as a Model of Total Electron Content: Performance and Diagnostics. Issue 11 (2nd November 2021) - Themens, D. R.; Reid, Ben; Jayachandran, P. T.; Larson, Bion; Koustov, A. V.; Elvidge, Sean; McCaffrey, A. M.; Watson, Chris
Abstract: Here, we assess to what extent the Empirical Canadian High Arctic Ionospheric Model (E‐CHAIM) can reproduce the climatological variations of vertical Total Electron Content (vTEC) in the Canadian sector. Within the auroral oval and polar cap, E‐CHAIM is found to exhibit Root Mean Square (RMS) errors in vTEC as low 0.4 TECU during solar minimum summer but as high as 5.0 TECU during solar maximum equinox conditions. These errors represent an improvement of up to 8.5 TECU over the errors of the International Reference Ionosphere (IRI) in the same region. At sub‐auroral latitudes, E‐CHAIM RMS errors range between 1.0 and 7.4 TECU, with greatest errors during the equinoxes at high solar activity. This represents an up to 0.5 TECU improvement over the IRI during summer but worse performance by up to 2.4 TECU during the winter. Comparisons of E‐CHAIM performance against in situ measurements from the European Space Agency's Swarm mission are also conducted, ultimately finding behavior consistent with that of vTEC. In contrast to the vTEC results, however, E‐CHAIM and the IRI exhibit comparable performance at Swarm altitudes, except within the polar cap, where the IRI exhibits systematic underestimation of electron density by up to 1.0 × 10 11 e/m 3 . Conjunctions with mid‐latitude ionosondes demonstrate that E‐CHAIM's errors appear to result from compounding same‐signed errors in its NmF2, hmF2, and topside thickness at these latitudes. Overall, E‐CHAIM exhibits strong performance within the polar cap and auroral oval but performs comparably to the IRI at sub‐auroral latitudes. Plain Language Summary: This study conducts a validation of the Empirical Canadian High Arctic Ionospheric Model (E‐CHAIM) in its representation of the column‐integrated plasma density of the ionosphere, which has important implications for radio communications and navigation technologies. The study finds that E‐CHAIM generally performs better than the International Reference Ionosphere in the polar cap and auroral region, but generally performs more comparably in sub‐auroral regions. Diagnosing these remaining errors using Swarm satellite measurements, the authors find that small errors in individual components of the model, when considered together, can result in larger errors when considering the overall performance of the model as a whole. Key Points: E‐CHAIM performs very well within the polar cap and auroral oval in the representation of TEC E‐CHAIM performance at sub‐auroral latitudes is comparable to that of the IRI Swarm and ionosonde observations show E‐CHAIM error results from the combined effect of several model components: hmF2, NmF2, and HTop